Bioarte: inferências e aplicabilidades nos campos da arte e suas intersecções biotecnológicas - Munhoz, Cássia Carinhato [UNESP]; Nicola, Ricardo Luís [UNESP] (My University, 2014)
Inspired by the effects of constant interdisciplinary interactions between art and science , this project intends to develop research instruments and analysis of the role of multimedia objects on visuality of biotechnology with a view to the application of hybrid concepts , ie transdisciplinary now , the cross-sectional nature of the newly bioart . Armed with broad investigative material, the research outlines for the apprehension of the subjects and objects bioartísticos with a view to their application in the project “ New Leonardos eSciences Institute of Innovation for living systems”, submitted to the call 016/2014 = MCTI / CNPq / CAPES / FAPS.

Inspirada pelos reflexos das constantes interações interdisciplinares entre arte e ciência, este projeto intenta desenvolver instrumentos de investigação e de análise do papel dos multimeios na visualidade dos objetos biotecnológicos com vistas à aplicação dos conceitos híbridos, ou seja, agora transdisciplinares, do caráter transversal da recém bioarte. De posse de amplo material investigativo, a pesquisa delineia para a apreensão dos sujeitos e objetos bioartísticos com vistas a sua aplicação no projeto “New Leonardos eSciences Institut of Innovation for living systems”, já submetido à chamada 016/2014 = MCTI/CNPq/CAPES/FAPS.
Bioart: investigations and applicability in the field of art and its biotechnological intersections
Keywords: Bioart; Art; Biotechnology; Trasndisciplinary studies; Hybridisms; eSciences; Bioart; Arte; Biotecnologia; Estudos Transdisciplinares; Hibridismos; eCiências